2020
DOI: 10.33369/jk.v4i1.10488
|View full text |Cite
|
Sign up to set email alerts
|

Studi Evaluasi Tentang Kompetensi Guru Penjasorkes Se Kabupaten Lampung Barat

Abstract: Penelitian ini bertujuan untuk mengetahui gambaran tentang kompetisi guru SD, SMP, SMA/SMK se-Kabupaten Lampung Barat. Tentang kompetisi Pedagogik, Keperibadian, Sosial, dan Profesional. Metode yang digunakan dalam penelitian ini menggunakan Deskriptif Kualitatif. Data dikumpulkan memalui wawancara, pengamatan, dokumentasi, dan angket. Berdasarkan hasil penelitian disimpulkan bahwa (1) Profil guru penjas bertugas di Kabupaten Lampung Barat dari faktor usia relatif tua, masa tugas cukup lama, (2) Aspek Kompetis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Different from the research results Azhari, H. (2020) who said that the understanding of PJOK teachers was quite good because in the implementation of PJOK learning the teachers still did not understand the material and also the characteristics of students. From the results of research conducted in West Lampung, it was found that PJOK teachers understand the characteristics of students, are able to make learning designs, are able to carry out learning in a conducive manner and are able to carry out continuous learning evaluations (Hermawan R, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Different from the research results Azhari, H. (2020) who said that the understanding of PJOK teachers was quite good because in the implementation of PJOK learning the teachers still did not understand the material and also the characteristics of students. From the results of research conducted in West Lampung, it was found that PJOK teachers understand the characteristics of students, are able to make learning designs, are able to carry out learning in a conducive manner and are able to carry out continuous learning evaluations (Hermawan R, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the readiness of prospective physical education teachers to social competence in order to be able to communicate and interact effectively and efficiently with students, fellow teachers, even guardians and the surrounding community. Teacher readiness competence in social aspects must be possessed by prospective teachers (Hermawan et al, 2020). Evidenced by the results of social competency readiness in Table 4 at point statement number 5, the number of respondents 21 (49%) in the strongly agree category.…”
Section: Readiness In Social Competencementioning
confidence: 94%
“…Tingkat kehadiran menjadi penting bagi dosen penjas, karena ini merupakan salah satu bentuk penerapan kompetensi kepribadian seorang pengajar penjas. Aspek Kompetisi Kepribadian menunjukkan prilaku yang dapat di teladani dan dicontoh peserta didik (Hermawan, Safei, & Utama, 2020). Berdasarkan data tersebut, dosen penjas IAIN Salatiga secara umum telah dipandang baik sebagai teladan oleh mahasiswa.…”
Section: Dipublikasikan Oleh : Upt Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan Muhammad Arsyad Al-banjari Banjarmasin 4unclassified